Comparison of 45-min nap versus no-nap during simulated night shift work on endothelial function: a randomized crossover feasibility trial - P. Daniel Patterson; Cassie J. Hilditch; Sarah E. Martin; David G. L. Roach; Matthew D. Weaver; Tiffany S. Okerman; David Hostler; Leonard S. Weiss; Steven E. Reis (Pilot and Feasibility Studies)
Abstract Background Night shift workers face increased risk of cardiovascular disease (CVD) compared to non-shift workers. Evidence supports on-shift napping and regular non-invasive monitoring of endothelial function for risk mitigation, yet neither strategy is widely used. Methods We evaluated the feasibility of non-invasive assessment of peripheral arterial tone (PAT) to assess the effect of napping during simulated night shift work on endothelial function. We used a single-site, randomized crossover trial of simulated night shift work with a 45-min nap condition versus a control, no-nap condition (ClinicalTrials.gov NCT05436951). Results The primary outcome was the number of participants with ≥ 70% of endothelial function assessments. Secondary outcomes included mean reactive hyperemia index (RHI), BP, and cognitive performance with the brief psychomotor vigilance task (PVT-B). Of the 10 consented, 9 completed both conditions. All participants exceeded feasibility benchmarks. Mean RHI did not differ by nap condition, and the delta from pre- to post measure did not differ (difference in delta =  − 0.26, 95% CI − 1.09, 0.58). Hourly PVT-B assessments from 19:00 to 07:00 h did not differ by nap condition. Compared to pre-nap measures, cognitive performance on the PVT-B was poorest at + 0 min post-nap. Conclusion Our findings can inform larger studies evaluating the effects of night shift work and napping on endothelial function. Trial registrations ClinicalTrials.gov (NCT05436951, registered on June 23, 2022).